Knowledge, attitudes and practices toward female genital schistosomiasis among community women and healthcare professionals in Kimpese region, Democratic Republic of Congo. - Cecilia Wangari Wambui; Joule Madinga; Mercy Gloria Ashepet; Maxson Kenneth Anyolitho; Patrick Mitashi; Tine Huyse (PLoS Neglected Tropical Diseases, 2024)
Background Chronic infection with Schistosoma haematobium causes female genital schistosomiasis (FGS), which leads to diverse lesions in the female genital tract and several complications, including infertility and a higher risk for HIV transmission. This study aims to understand the knowledge, attitudes, and practices (KAP) toward FGS and associated factors among women and health professionals in the schistosomiasis endemic focus of Kimpese, western Democratic Republic of Congo (DRC). Methods In January 2022, two semi-quantitative questionnaires were administered to 201 randomly selected community women in Kifua II village, and to purposely selected health professionals (20 nurses and 41 doctors) from Kimpese Health Zone. KAP statements were coded using Likert scale, summarized as frequencies and percentages, and assessed for internal reliability using Cronbach's alpha. Associations between the socio-demographic characteristics of respondents and the KAP variables were assessed using Pearson chi-square (χ2) test, Cramer's V (φ) and gamma (γ) coefficients. Results Overall, respondents had high knowledge of schistosomiasis in general but low FGS-specific knowledge (91% versus 45%). Misconceptions concerned the disease transmission, with 30.3% of women and 25% of the nurses believing that FGS is transmitted by drinking untreated water, while 26.8% of the doctors mentioned sexual contact as a mode of FGS transmission. Negative attitudes included considering FGS not a very serious disease (34.8%), feeling uncomfortable during gynaecological examination (35.3%), difficulties avoiding risky water contact (72.1%) and open defecation/urination (41.3%), not intending to share FGS status with their husbands (38.3%) and loved ones (63.6%), and believing that husbands would leave them if they were infertile (31.8%). Regarding practices, 77.6% of women engaged daily in activities involving contact with water. Practices of health professionals were hampered by the lack of equipment and specialized knowledge for FGS diagnosis with only 57% of healthcare workers having a microscope in their facilities. Women's KAPs varied by age, education, marital status, occupation and monthly income. Conclusion This study highlights insufficient knowledge, existing negative attitudes, at risk practices towards FGS by women, and limitations of FGS management by health professionals. These findings can help for tailored health education and WASH strategies, and call for health professional's capacities reinforcement.